Pesan Moral Dalam Film Di Bawah Umur (Analisis Semiotika Pada Film Di Bawah Umur) - Salsabila, Lataniya Rizki; Syarief, Fauzi; Marulitua A, Bonardo (CV. ITTC INDONESIA, 2023)
Communication is conveying messages or information from one media to another media, either directly or indirectly, known as communication. Mass media and official channels function to spread news and messages to a wide audience. In the context of electronic media, media is a modern electronic tool that allows many people to convey messages to each other. The number of people involved in mass communication is increasing every day. This is the result of technological developments that continue to improve every day. Researchers used a qualitative approach in this research. states that qualitative research is research that seeks to understand phenomena from the experiences of people being examined thoroughly, such as behavior, observations, motivations, actions, etc. with the help of verbal descriptions and language, in specific natural contexts, and with various scientific methods. The results of the research above show that underage films—especially teenagers—capture the phenomenon of promiscuity among teenagers. This is quite clear from several scenes above, such as in scene 1 when Aryo, Dani, and Rafi skip class during school hours and they regret their actions. In scene 2 it is about the misunderstanding between Aryo and Kevin which makes them fight. In scene 3 it is also about the misunderstanding between Marsya and Lana even though the problem between the two of them can be discussed well. In scene 4 it is about the misunderstanding between Aryo and Marsya, their problem should also be discussed carefully too. In scene 5 it is about the problem of Aryo getting Naya pregnant even though in fact it was Bayu who got Naya pregnant. In scene 6 it is about Bayu's problem, it turns out he was the one who got Naya pregnant, at first Bayu didn't want to be honest and finally he was honest that he was actually the one who got Naya pregnant and there Bayu regretted his actions and apologized to Aryo and his friends. After conducted research on the film Under Age using Roland Barthes' semiotic analysis which is divided into 3 concepts: denotation, connotation and myth. Researchers can draw the conclusion that there is a meaningful moral message in the film Underage. What is found in Aryo's character is: stubborn and selfish. Meanwhile, Lana's character is: gentle, kind and forgiving. And the moral message is to be smarter in choosing friends so that we don't have a bad impact on teenagers' relationships.